Correction to: "For the Eradication of Polish and Jewish-Muscovite Rule in Ukraine": An Examination of the Crimes of the Ukrainian Legion of Self-Defense (Holocaust and genocide studies, 2022)
In the originally published version of this manuscript, there were two errors in the rank ascribed to Karl Pütz. This should read (p.452, p.457): "Sturmban